2016
DOI: 10.1186/s13033-016-0107-1
|View full text |Cite|
|
Sign up to set email alerts
|

Walking the tightrope-perspectives on local politicians’ role in implementing a national social care policy on evidence-based practice

Abstract: BackgroundDespite national policy recommending evidence-based practice (EBP), its application in social care has been limited. While local politicians can affect the process, little is known about their knowledge, attitudes and roles regarding EBP. The aim here is twofold: to explore the role of local politicians in the implementation of EBP in social care from both their own and a management perspective; and to examine factors politicians perceive as affecting their decisions and actions concerning the implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…In line with this study, previous research has shown that both knowledge and attitudes are important for practices and behaviors. A study on Swedish local politicians' views on their role in the implementation of evidenced-based practice in social care in municipalities found that a personal interest and knowledge were important for how they viewed their roles and what actions they took (Bäck et al 2016). A study on municipalities in Finland in the 1990s questioned the association between politicians' attitudes and outcomes in priority setting and resource allocation within health care (Lammintakanen and Kinnunen 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this study, previous research has shown that both knowledge and attitudes are important for practices and behaviors. A study on Swedish local politicians' views on their role in the implementation of evidenced-based practice in social care in municipalities found that a personal interest and knowledge were important for how they viewed their roles and what actions they took (Bäck et al 2016). A study on municipalities in Finland in the 1990s questioned the association between politicians' attitudes and outcomes in priority setting and resource allocation within health care (Lammintakanen and Kinnunen 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, little research on politicians' role in health promotion has been conducted to date. Moreover, the focus has often been on priority setting and resource allocation (Garpenby and Nedlund 2016;Rosén et al 2014) or on the implementation of evidence-based practice (Bäck et al 2016). Although political ideology and political will have been suggested as important factors for achieving health equity (Bryant 2010), they have not been investigated as systematically as other health-promoting factors (Catford 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the original version of this article [ 1 ] one of the quotations was unfortunately misattributed. The first quotation “It’s more about having an interest in the issues and familiarizing yourself with the working methods and the target group, and so forth.…”
Section: Correction To: Int J Ment Health Syst (2016) 10:75 Https://doiorg/101186/s13033-016–0107-1mentioning
confidence: 99%
“…Det centrala är dock att det finns intresse och att det läggs ner ansträngningar på att utveckla och diskutera stödets innehåll, och här är både den politiska nivån och förvaltningen inom kommunernas socialtjänst viktiga aktörer. Det finns studier som visar på otydlighet i fråga om ansvaret för en kunskapsbaserad socialtjänst mellan dessa nivåer, men också tecken på att intresset för frågorna ökar (Bäck et al, 2016;Socialstyrelsen, 2017b).…”
Section: Avslutning: Ett Moget Verksamhetsfält?unclassified